2022
DOI: 10.1007/s13337-022-00795-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors enhancing the transmission of mosquito-borne arboviruses in Africa

Abstract: Arthropod-borne viruses (Arboviruses) replicate in vertebrates and invertebrates and are mainly transmitted by mosquitoes. Between 2000 and 2021, several arbovirus outbreaks were recorded in African countries, including dengue, yellow fever, Chikungunya, Zika, and O’nyong nyong. Most often, the causes and factors involved in these outbreaks are unknown. We aimed to understand current knowledge regarding factors responsible for the persistent transmission and emergence of mosquito-borne arboviruses in Africa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Furthermore, deforestation can alter the availability and quality of larval habitats for different mosquito species, as well as the distribution and abundance of their hosts and predators. A study in Brazil found that deforestation increased the abundance of Anopheles darlingi, a major malaria vector, by creating more suitable breeding sites [32]. Lastly, spatial and temporal patterns of mosquito population dynamics, which are influenced by various environmental and biological factors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, deforestation can alter the availability and quality of larval habitats for different mosquito species, as well as the distribution and abundance of their hosts and predators. A study in Brazil found that deforestation increased the abundance of Anopheles darlingi, a major malaria vector, by creating more suitable breeding sites [32]. Lastly, spatial and temporal patterns of mosquito population dynamics, which are influenced by various environmental and biological factors.…”
Section: Resultsmentioning
confidence: 99%
“…Much of the increase in these diseases has been attributed to habitat expansion due to climate change and widespread insecticide resistance ( 4 ). Insecticide resistance is arguably one of the most significant challenges for pest control professionals today and plagues the public health, agricultural, and urban pest control sectors ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive attempts to help contain or eradicate their outbreaks, the majority of arboviral diseases continue to be more prevalent in Africa for a variety of reasons [4,5]. Arboviral illnesses are not exempt from concerns about public health.…”
Section: Introductionmentioning
confidence: 99%